Development of the Pectoral Lobed Fin in the Australian Lungfish Neoceratodus forsteri - Hirasawa, Tatsuya; Cupello, Camila; Brito, Paulo M.; Yabumoto, Yoshitaka; Isogai, Sumio; Hoshino, Masato; Uesugi, Kentaro (Frontiers in Ecology and Evolution, 2021)
The evolutionary transition from paired fins to limbs involved the establishment of a set of limb muscles as an evolutionary novelty. In parallel, there was a change in the topography of the spinal nerves innervating appendicular muscles, so that distinct plexuses were formed at the bases of limbs. However, the key developmental changes that brought about this evolutionary novelty have remained elusive due to a lack of data on the development of lobe fins. Here, we observed the development of the pectoral fin in the Australian lungfish Neoceratodus forsteri through synchrotron radiation X-ray microtomography. Neoceratodus forsteri is a key taxon for understanding the fin-to-limb transition due to its close relation to tetrapods and well-developed lobe fins. At the onset of the fin bud in N. forsteri, there is substantially no mesenchyme at the junction between the axial body wall and the fin bud, which corresponds to the embryonic position of the brachial plexus formed in the mesenchyme in tetrapods. Later, concurrent with the cartilage formation in the fin skeleton, the fin adductor and abductor muscles become differentiated within the surface ectoderm of the fin bud. Subsequently, the girdle muscle, which is homologous to the tetrapod serratus muscle, newly develops at the junction between the axial body wall and the fin. Our study suggests that the acquisition of embryonic mesenchyme at the junction between the axial body wall and the appendicular bud opened the door to the formation of the brachial plexus and the specialization of individual muscles in the lineage that gave rise to tetrapods.